1987
DOI: 10.1364/ao.26.003315
|View full text |Cite
|
Sign up to set email alerts
|

Automated densitometry of cell populations in a continuous-motion imaging cell scanner

Abstract: Continuous-motion imaging provides a method for the rapid quantitative analysis of slide-mounted cell preparations. Densitometric and morphometric cellular features can be measured and used to classify individual cells. Tests on the densitometric accuracy of the CERVIFIP CMI system show a c.v. of 6.5% for diploid mouse hepatocytes and a measuring rate of up to 500 cells/sec. CMI is particularly useful for problems requiring the interactive analysis of rare cell types and for the measurement of morphological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Dr Husain's interest in automation provoked attempts to standardise the samples that could be subjected to microscopic and automated analysis. Examples include the development of vaginal irrigation/cytopipette as sampling methods, various cell preparation techniques as well as recognising the issues arising from the implementation of new technology such as the cross‐contamination of specimens . He continued an involvement with automation throughout his career .…”
Section: Cytology Automation and Cell Preparationmentioning
confidence: 99%
“…Dr Husain's interest in automation provoked attempts to standardise the samples that could be subjected to microscopic and automated analysis. Examples include the development of vaginal irrigation/cytopipette as sampling methods, various cell preparation techniques as well as recognising the issues arising from the implementation of new technology such as the cross‐contamination of specimens . He continued an involvement with automation throughout his career .…”
Section: Cytology Automation and Cell Preparationmentioning
confidence: 99%
“…The IOD for each isolated nucleus is calculated as the sum of the individual pixel ODs within the segmented object area, corrected by a skirt value [12] to compensate for the background. The skirt value for a segmented object is calculated from the difference between two dilated objects, the larger obtained by Euclidean dilation of the corresponding nucleus by a radius 4 disc, and the smaller one by a disc of radius 2.…”
Section: Three-dimensional Segmentation and Densitometric Measurementmentioning
confidence: 99%
“…The intensity values of each pixel were transformed to optical density (OD) values prior to analysis. This OD transformation was carried out by table look up, using a calibration table obtained by measurements on a photographic test slide which had previously been measured on a microdensitometer [7,12]. Figure 2 shows an example of sections of a typical pair of nuclei which are completely overlapped (only 24 middle sections are shown).…”
Section: Experimental Measurement Proceduresmentioning
confidence: 99%
“…The system by Castleman 17 apparently paused to perform static autofocus at regular intervals, and those by Shippey et al 18 and Tucker et al 19,20 autofocused dynamically during scanning. Both Shippey et al 18 and Netten et al 16 reported that the focus error was greater than the depth of field, and Tucker et al 19 reported that a 1-m focus error produced a 12% error in the integrated optical density of the cell nucleus. Autofocus accuracy was reported to be very dependent on the density of cells by Castleman, 17 and the need for many cells in each field of view was common to all of the systems that included autofocus.…”
Section: Introductionmentioning
confidence: 99%